(untitled) (PANGEEA, 2025)
Brief remarks on the origin of place names Criş, Bihor, Zărand, Ardeal, Transilvania, Bărăgan and Baraolt. In the name of some places of Romania, there are some data that recall the distant past and whose etymology and semantics I tried to explain.